2017
DOI: 10.1177/1178632917701123
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Community Leaders in the Development of a Cardiovascular Health Behavior Survey Using Focus Group–Based Cognitive Interviewing

Abstract: Establishing the validity of health behavior surveys used in community-based participatory research (CBPR) in diverse populations is often overlooked. A novel, group-based cognitive interviewing method was used to obtain qualitative data for tailoring a survey instrument designed to identify barriers to improved cardiovascular health in at-risk populations in Washington, DC. A focus group–based cognitive interview was conducted to assess item comprehension, recall, and interpretation and to establish the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…To support the feminist research principles used throughout this mixed methods study and described in Keedle et al (2019) [17], it was imperative to involve potential survey participants in the co-design and pilot testing of the survey [34]. This was achieved using online cognitive focus groups [35].…”
Section: Pilot Testing Of the Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…To support the feminist research principles used throughout this mixed methods study and described in Keedle et al (2019) [17], it was imperative to involve potential survey participants in the co-design and pilot testing of the survey [34]. This was achieved using online cognitive focus groups [35].…”
Section: Pilot Testing Of the Surveymentioning
confidence: 99%
“…Cognitive focus groups have developed from cognitive interviewing which aims to understand the responses of survey questions by analysing the comprehension, recall, decisions and judgement and response processes of targeted participants [35][36][37][38]. Recruitment for the focus groups included social media pregnancy and parenting groups where women were asked to contact the researcher if interested in testing the survey and participating in focus groups.…”
Section: Pilot Testing Of the Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The focus group was audiorecorded, and the recording was transcribed verbatim by an independent clinical research organization (Social Solutions International, Inc, Silver Spring, MD, USA). The discussion of reliability checks of the transcribing process, development of a codebook of themes, the coding process, and evaluation of the trustworthiness of qualitative analyses are available in previously published work [ 30 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eight individuals from the target population were recruited to take the survey and test the device to ensure that the study instruments (survey and PA tracker) conveyed our intended meanings. The feedback received from the focus group participants provided feedback to the study group that identified possible barriers in completing the survey, such as unclear language in the survey questions [ 11 ].…”
Section: Methodsmentioning
confidence: 99%